SOCIAL CONSTRUCTION OF POWERFUL WOMEN TO FIGHT AGAINST CRIMINAL ACTS IN JOSEPH McGINTY NICHOL’S CHARLIE’S ANGELS MOVIE (2000) : A FEMINIST APPROACH - HIKMAH , DITANIA ALFI (2010)
The object of the study is a movie Charlie’s Angels directed by Joseph McGinty Nichol. The study is to reveal how social construction of powerful women is reflected in Charlie’s Angels directed by Joseph McGinty Nichol published in 2000. The objective of the study is to analyze the structural elements in the movie and to analyze social construction of powerful women of the movie based on feminist approach. The researcher employs the descriptive qualitative research as a type of the research. The data sources divided into two, namely primary data source and secondary data source. The primary data source is the events of the movie and script of Charlie’S Angels and the secondary data source is biography of character. The method of collecting data is documentation. The technique of analyzing data is descriptive. The result of the study is as follows. First, based on the structural analysis, Joseph McGinty Nichol delivers a moral message that women and men have equal opportunity against the criminal acts and the structural elements are related each other and form a unity. Second, based on the feminist analysis, Joseph McGinty Nichol reflects gender injustice in the society and criticizes the society that places women and men unequal.